DEVELOPMENT AND FORMS OF INTERNATIONAL CURRENCY RELATIONS IN COMMERCIAL BANKS OF THE REPUBLIC OF UZBEKISTAN - Tokhtayeva Umida Shamsiddin kizi (American Journals, 2024)
This article discusses the economic nature of the global financial market, its social features and its theoretical and methodological aspects, its main and additional functions and principles, the implementation of market instruments, and is scientifically based from the perspective of participating institutions. to perform the functions of its peculiarities.
Keywords: Global financial market, international financial market, capital accumulation, redistribution, debt capital, debt instruments, derivative contracts, euro market, methodological approach, interests of economic agents.